The surgical anatomy of the perineum. (1st March 2013) - Mahadevan, V; Chandak, P
Abstract : The anatomy of the perineum and pelvis is complex. Those outside the specialist fields of colorectal surgery, urology and gynaecological surgery often have a less-than-complete understanding of the anatomical details of this region. The recent increase in complicated pelvic and perineal injuries caused by the detonation of Improvised Explosive Devices has brought into sharp focus, the importance of this area of surgical anatomy. The following article describes, in a systematic and detailed manner, the anatomy of the urogenital and anal regions of the perineum. The terminology in relation to the fascial layers and structures encountered in the perineum is elucidated. In addition, the surgical anatomy of the scrotum and its contents and the ligamentous support of the penis are described, with clear illustrations throughout. It is intended that this article will go some way towards clarifying the anatomy underlying the surgical management of complex perineal/pelvic injuries, and benefit both the specialist and non-specialist military surgeon.